Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Menggunakan Model Role Playing di Kelas IV SD Negeri 03 Lubuak Batingkok Kabupaten Lima Puluh Kota - Ramadani, Anggun; Masniladevi, Masniladevi; Reinita, Reinita; Fitria, Yanti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe how to improve student learning outcomes in Pancasila Education learning using the Role Playing model in grade IV of SD Negeri 03 Lubuak Batingkok, Fifty Cities Regency. This type of research is Classroom Action Research (PTK) using qualitative and quantitative approaches. This research was carried out in two cycles, with research procedures consisting of planning, implementation, observation, and reflection. The subjects of this study are classroom teachers as observers, researchers as practitioners or teachers, and 16 students of grade IV SD Negeri 03 Lubuak Batingkok. The data collection techniques used are tests and non-tests, namely tests of learning outcomes, observation, and documentation. The data produced was analyzed quantitatively and qualitatively. The results of the study show that the Role Playing model can improve students' learning outcomes in Pancasila Education learning in grade IV of SD Negeri 03 Lubuak Batingkok, Fifty Cities Regency